Digital Storytelling Video to Analyze Students Concept Mastery and Creativity in Learning Food Additives Topic - Putri, Weni Anissa; Sanjaya, Yayan; -, Eliyawati (Asian Journal of Science Education, 2021)
The students have learning difficulties in learning science because their concept mastery and creativity were low. Digital storytelling is good media for students who make their own story. The research was conducted to identify students concept mastery and creativity by digital storytelling video in learning food additives. The method used in this research is weak experiment. The sample of 36 students from private school in Cianjur, West Java. The students concept mastery was measured by objective test based on bloom taxonomy. Objective test contained of multiple choices. Data analysis was using SPSS. The students creativity is measured by Creative Product Semantic Scale (CPSS) rubric based on three dimensions such as novelty, resolution, elaboration and synthesis. The result of students concept mastery is N-Gain is 0.30 categorized as medium improvement. The results of students creativity are resolution is (54%), categorized as very low, revolution is (61%) categorized as medium. elaboration and synthesis is (66%) categorized as medium. Based on this result, Digital storytelling video can be utilized for students concept mastery and students creativity.